Sustainable Facility Design: A Case Study on Energy-Efficient Plant Layouts - Sekarwati, Nadira (Journal of Sustainability Industrial Engineering and Management System, 2023)
This study aims to explore the role of sustainable facility design in enhancing energy efficiency within industrial environments, with a particular focus on plant layout configurations. Amid increasing environmental regulations and economic pressures, optimizing spatial arrangements in manufacturing facilities has emerged as a strategic pathway toward reducing energy consumption and supporting broader sustainability goals. Employing a qualitative literature-based research methodology, this study synthesizes findings from approximately 45 peer-reviewed articles, policy reports, and industrial case studies published between 2010 and 2024. The research adopts an interpretivist epistemology and applies thematic content analysis to identify key concepts, strategies, and barriers associated with energy-efficient facility layouts. Findings reveal that spatial configuration significantly affects energy performance, influencing variables such as lighting, HVAC demand, and material transport distances. Technological integration, particularly through digital simulation tools and Industry 4.0 technologies like IoT and digital twins, further enhances layout optimization by enabling real-time energy monitoring and adaptive control. The analysis also underscores that energy-efficient layouts generate economic co-benefits, including reduced utility costs and improved production throughput. However, implementation barriers persist, notably in small- and medium-sized enterprises due to financial constraints, technical knowledge gaps, and organizational resistance to change. The study concludes that energy-efficient facility layouts are not only feasible but essential for sustainable manufacturing, offering a synergistic solution that aligns operational efficiency with environmental stewardship. It advocates for proactive, data-driven layout planning supported by cross-functional collaboration and policy incentives.